PEMANFAATAN RAGI (SACCAROMYCES SP.) DALAM PENGENDALIAN PENYAKIT TUMBUHAN YANG RAMAH LINGKUNGAN - Khalimi, Khamdan (Bumi Lestari Journal of Environment, 2010)
One of the most important challenges is preventing and controlling pest and diseases problems, which can partly or completely ruin agricultural crops. Survey done in Bali at three main vanilla growing areas indicated that the stem rot disease was the main and the most destructive disease on vanilla. The objective of the research is to control the vanilla stem rot disease caused by pathogenic fungus Fusarium oxysporum f, sp.vanillae. The test for antagonistic activity by fungi was done through side by side culture and antifungal activity test on vanilla seedlings. Results of this study showed that Saccaromyces sp.effectively suppressed the growth of fungi on Potato Dextrose Agar medium and vanilla seedlings.
Keywords: saccaromyces sp.; control the plant disease